Pledge on shares in companies that are owners or perpetual usufructuaries of agricultural real estate – a paradox of Clause 3a of Article 3a of the Act on shaping the agricultural system - Bieluk, Jerzy (Przegląd Prawa Rolnego, 2021)
Since 30 April 2016, the rigours of the Act on shaping the agricultural system have been extended to cover, inter alia, trading in shares in companies. Pursuant to the provision of Article 3a(1) of the Act, the National Support Centre for Agriculture acting on behalf of the State Treasury has the right of first refusal to purchase shares in a company which is the owner or a perpetual usufructuary of an agricultural real estate with an area of at least 5 ha or an agricultural real estate with a total area of at least 5 ha. The amendment of the aforementioned Act introduced by the Act of 26 April 2019 amending the Act on shaping the agricultural system and some other acts, is clause 3a added to Article 3a, under which, in the event that shares are encumbered with the right of pledge and the payment of the price is already due, the National Support Centre for Agriculture must pay the price within 14 days from the date of receipt of a notice on the expiry of the pledge. This solution results in consequences not foreseen by the legislator, in some cases preventing receipt of the price for shares from the Centre. This restriction affects the payment of the price and raises serious doubts as to its compliance with the Constitution of the Republic of Poland, since it may lead to a situation where shares are taken over without due compensation paid.